The Actualization of Civic Education as a Solid Foundation for Youth in Countering Secularism - Anggriawan, Kevlin; Ahmad, Endang; Nurgiansah, T Heru (CV. Rayyan Dwi Bharata, 2024)
Civic Education holds significant importance as a scientific field in cultivating the moral values of the Indonesian population and shaping the future image of the country. In the present era, there is an urgent need for Civic Education among the Indonesian people, particularly the youth, to establish a solid national foundation and develop noble character traits that will protect them from the influence of secularism pervading society. Secularism is viewed as a formidable adversary to the Indonesian people, and it is crucial to prevent the younger generation from embracing such ideas within the boundaries of the Indonesian state. This article adopts a literature review approach, incorporating articles from various credible sources such as SAGE Journal, Google Scholar, and relevant books, in order to enhance the credibility and accuracy of the research findings. The outcomes of this study will comprehensively illustrate the implementation of Civic Education as a means to empower youth in firmly opposing the spread of secularism in Indonesia. The role of youth in shaping the nation's civilization is of utmost significance, as they serve as the vanguard in safeguarding against the encroachment of secularism and strive towards realizing the national ideals of independence, unity, sovereignty, justice, and prosperity